Beer–The Importance of Colloidal Stability (Non-Biological Haze) - Kristina Mastanjević; Vinko Krstanović; Jasmina Lukinac; Marko Jukić; Zdravko Vulin; Krešimir Mastanjević (Fermentation, 2018)
Today’s beer differs in many ways from the original hazy brew made from grains and water left in the sun to ferment. The development of brewing procedures introduced filtration and colloidal stabilization as key elements in beer preservation and stability. Colloidal stability of beer is the most important factor in beer quality. Colloidal particles significantly shorten beer’s storage time, but most importantly, also influence its appearance. Colloidal stabilization involves one or more procedures that are applied at different stages during production and result in colloidal stability of the final product. Beer is considered to be colloidal stable if it can be stored for several months at 25 °C without exhibiting any changes in composition or other properties; specifically, beer has to be able to remain clear without any signs of precipitation. Since colloidal stability is of primary importance for the consumer, retail requirements have resulted in many solutions for this issue. Stabilization agents have to be reliable during the filtration and stabilization processes. Additionally, renewable agents are highly desirable. The level of colloidal stability required depends on the desired storage time and temperature after the beer has been packed. Consumers have higher and higher expectations that the industry has to follow.